Faux et usage de faux : la forme de l’archive dans « The Narrative of Jacobus Coetzee », de J. M. Coetzee - Odile Gannier (Amnis)
« The only thing that someone exceptionally suspicious could have against this relation and its reliability is that Mr Kolben might have embellished the Hottentots answers, due to his vivid imagination, and used some flowers of rhetoric that many people consider as essential in order to make a narrative interesting, especially when it deals with so rude tribes. » In 1741, the translator’s preface of Description of the Cape of Good Hope by Kolben already undermines a yet first-hand testimony. The memoirs and travel stories convey a large range of considerations about natural history, about habits and customs of encountered populations, sometimes colonized ones. J. M. Coetzee chooses to adopt the form of a narrative of archive, which was attributed to his arch-father during a travel in Namaqua territory, in southern Africa, with the aim of an elephant hunt, and then during the punitive expedition that followed. These papers describe how the situation quickly deteriorates between several completely foreign communities. The narrative takes place in the 1760’s, which explains the blatant gap in the mutual consideration of the Boers, the Hottentots and the Bochiman. What is puzzling in this short story, integrated to The Dusklands is the status of the text: is the arch-father’s narrative, whose speech is openly racist, genuine? Is it actually a set-up, with the subtlety of the preface, the acknowledgments, meant for making believe that the testimony is real? The reader has to make the interpretative work about the form himself in order to decide of the ideological meaning of the text.